Chiral emissive porous organic cages. Issue 3 (12th December 2022) - Sun, Yu-Ling; Wang, Zhen; Ma, Hui; Zhang, Qing-Pu; Yang, Bin-Bin; Meng, Xianggao; Zhang, Yaohua; Zhang, Chun
Abstract : A pair of chiral, emissive and porous tubular multi-functional organic molecular cages were synthesized easily by imine chemistry of 4, 4′, 4′′, 4′′′-(ethene-1, 1, 2, 2-tetrayl)-tetrabenzaldehyde (ETTBA) with ( R, R )- or ( S, S )-diaminocyclohexane (CHDA). Abstract : A pair of chiral, emissive and porous tubular multi-functional organic molecular cages were synthesized easily by imine chemistry of 4, 4′, 4′′, 4′′′-(ethene-1, 1, 2, 2-tetrayl)-tetrabenzaldehyde (ETTBA) with ( R, R )- or ( S, S )-diaminocyclohexane (CHDA). It was found that the chirality of CHDA was transferred and amplified to tetraphenylethylene (TPE) in the process of formation of cages, which further endowed the cages with circularly polarized luminescence (CPL) characteristics. As a result of the synergy of the chirality and porous structure in the solid state, both cages exhibited a good chiral adsorption enantioselectivity to a series of aromatic racemates.